The Influence of Leadership Style and Organizational Culture on Organizational Performance Mediated by Employee Motivation: A Study of Puskesmas in the Eastern Region of Bandung City - Ryan Rizqi Rahman; Nurul Hermina (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to examine the influence of leadership style and organizational culture on employee motivation and organizational performance at Puskesmas located in East Bandung City uses a quantitative approach. A total of 220 employees from 18 Puskesmas in East Bandung City participated in the survey, with data collection conducted through questionnaires. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 3.2.9 software, which focuses on hypothesis testing and bootstrapping to assess the relationship between variables. This study found that leadership style and organizational culture have a positive and significant effect on employee motivation, which in turn affects organizational performance and confirms the mediating role of motivation between leadership style and organizational performance, as well as between organizational culture and organizational performance. The statistical results show significant t-statistics and p-values, indicating strong predictive relevance of the model. However, the indirect effect through motivation is relatively moderate, indicating that further efforts are needed to strengthen the relationship in improving organizational performance. In particular, the research results highlight the need for better motivational strategies in Puskesmas to achieve more optimal organizational performance.